GA For Optimal PI in DC Voltage Regulation of D-STATCOM. - Perumandla Sadanandam (International Journal of Electrical and Computer Engineering (IJECE), 2011)
The performance of DSTATCOM depends on a DC capacitor voltage regulation.The regulation of DC capacitor voltage based on optimal PI coefficients. The conventional method to determine PI coefficients is trial and error method. In this paper Genetic Alogorithem is applied for exact calculation of optimized PI coefficients can carried out to reduce disturbances in DC link voltage. Optimizations and simulations are worked out in MATLAB environment. DOI:http://dx.doi.org/10.11591/ijece.v1i2.91